Direct reduced iron and zinc recovery from electric arc furnace dust. Issue 12 (11th August 2022) - Matsukevich, Iryna; Kulinich, Natalia; Romanovski, Valentin
Abstract: BACKGROUND: At present, the volumes of use of electric arc furnace (EAF) dust are extremely insignificant. The volumes of their formation amount to thousands of tons per month. During storage, they have a negative impact on the environment. At the same time they are a material that has a valuable composition (oxides of iron, non‐ferrous metals, etc.) and is promising for recycling. However, the secondary use of zinc‐containing EAF dust in ferrous metallurgy leads to the accumulation of zinc in the lining of blast furnaces and frequent malfunctions. RESULTS: It has been established that zinc oxide is mainly in the bound state in the composition of the franklinite phase (Zn, Mn, Fe)(Fe, Mn)2 O4 . The processes of solid‐phase reduction of EAF dust with the production of zinc concentrate and sponge iron, which are in demand as raw materials for non‐ferrous and ferrous metallurgy, have been studied. The optimal conditions for the reduction process were determined and the physicochemical characteristics, granulometric and phase composition of the initial materials, and reduction products were investigated. CONCLUSIONS: It has been established that the use of a combination of reducing agents of different nature (coal coke and H2 ) during heat treatment at 1100 °C and cooling in a reducing medium (Ar/H2, 5 vol%) makes it possible to obtain sponge iron with impurities (the highest degree of iron metallization was 97.5%), and zinc oxide with a basic substance content of about 98.4 wt.%. © 2022 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).